Measurements of differential cross sections of top quark pair production as a function of kinematic event variables in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2018)
Measurements of differential t (t) over bar production cross sections are presented in the single-lepton decay channel, as a function of a number of kinematic event variables. The measurements are performed with proton-proton collision data at root s = 13 TeV, collected by the CMS experiment at the LHC during 2016, with an integrated luminosity of 35.9 fb(-1). The data are compared to a variety of state-of-the-art leading-order and next-to-leading order t (t) over bar simulations.